Case Report: Interventricular Septal Hematoma Complicating Left Bundle Branch Pacing Lead Implantation - Zheng, Rujie; Wu, Shengjie; Wang, Songjie; Su, Lan; Ellenbogen, Kenneth A.; Huang, Weijian (Frontiers in Cardiovascular Medicine, 2021)
Background: Left bundle branch pacing (LBBP) is a novel physiological pacing and previous studies have confirmed the feasibility and safety of it. The incidence of complications in LBBP is relatively low as reported. Here we present a case of interventricular septal hematoma complicating LBBP lead implantation. Case summary: LBBP was achieved for treatment of high-grade atrioventricular block in a 67-year-old female. Chest pain began 1 h after implantation when the electrocardiogram showed ST-T changes. Then bedside echocardiography confirmed the formation of interventricular septal hematoma. Urgent coronary angiography showed the contrast agent retention and overflow in the interventricular septum. The symptom was relieved half an hour later. Echocardiogram performed 2 h later revealed the size of the hematoma was the same as before. The electrocardiography, coronary angiography and CTA confirmed the resolution of the hematoma at 1-month follow-up. Pacing parameters and cardiac function remained stable during 6-month follow-up. Conclusion: This is the first reported case describing the clinic features and management of interventricular septum hematoma complicating LBBP. The importance of routine echocardiograms after implantation for identifying the hematoma should be highlighted.